Experimental infection of Japanese macaques with simian retrovirus 5. (4th January 2019) - Koide, Rie; Yoshikawa, Rokusuke; Okamoto, Munehiro; Sakaguchi, Shoichi; Suzuki, Juri; Isa, Tadashi; Nakagawa, So; Sakawaki, Hiromi; Miura, Tomoyuki; Miyazawa, Takayuki
Abstract : Recently, a large number of Japanese macaques ( Macaca fuscata ) died of an unknown hemorrhagic syndrome at Kyoto University Primate Research Institute (KUPRI) and an external breeding facility for National Institute for Physiological Sciences (NIPS). We previously reported that the hemorrhagic syndrome of Japanese macaques at KUPRI was caused by infection with simian retrovirus 4 (SRV-4); however, the cause of similar diseases that occurred at the external breeding facility for NIPS was still unknown. In this study, we isolated SRV-5 from Japanese macaques exhibiting thrombocytopenia and then constructed an infectious molecular clone of the SRV-5 isolate. When the SRV-5 isolate was inoculated into two Japanese macaques, severe thrombocytopenia was induced in one of two macaques within 22 days after inoculation. Similarly, the clone-derived virus was inoculated into the other two Japanese macaques, and one of two macaques developed severe thrombocytopenia within 22 days. On the other hand, the remaining two of four macaques survived as asymptomatic carriers even after administering an immunosuppressive agent, dexamethasone. As determined by real-time PCR, SRV-5 infected a variety of tissues in Japanese macaques, especially in digestive and lymph organs. We also identified the SRV-5 receptor as ASCT2, a neutral amino acid transporter in Japanese macaques. Taken together, we conclude that the causative agent of hemorrhagic syndrome occurred at the external breeding facility for NIPS was SRV-5.